EMPOWERING KLATEN BAMAGNAS COMMUNITY THROUGH DIGITAL MARKETING TRAINING - Ricky; Tarigan, Ruth Srininta; Proboyo, Adelina; Maer, Maria Natalia Damayanti; Soetanto, Tessa (SUBAKTYA: UNPAR COMMUNITY SERVICE JOURNAL, 2025)
To support the digital transformation program from the Ministry of Religious Af airs, BAMAGNAS in Klaten acknowledged the necessity of providing its members with the knowledge that is essential to thrive in the modern digital economy. This knowledge can be taught to their congregation afterwards, particularly in digital marketing, so that they can establish a successful and sustainable business in this digital era. This workshop aimed to teach participants about the significance of digital marketing, including online promotion, how to use promotional  media effectively, and how to create engaging content. The workshop taught participants how to use social media platforms like Shopee and Instagram and to produce visually appealing content. The training approaches used are presentations, interactive group discussions, and  practical activities for all participants. At the end of the training, results showed an improvement in participants' understanding of the  necessity of digital marketing and the creation of interesting promotional content.